2004
DOI: 10.1111/j.0022-2720.2004.01318.x
|View full text |Cite
|
Sign up to set email alerts
|

Probing plasma membrane microdomains in cowpea protoplasts using lipidated GFP‐fusion proteins and multimode FRET microscopy

Abstract: SummaryMultimode fluorescence resonance energy transfer (FRET) microscopy was applied to study the plasma membrane organization using different lipidated green fluorescent protein (GFP)-fusion proteins co-expressed in cowpea protoplasts. Cyan fluorescent protein (CFP) was fused to the hyper variable region of a small maize GTPase (ROP7) and yellow fluorescent protein (YFP) was fused to the N-myristoylation motif of the calcium-dependent protein kinase 1 ( Le CPK1) of tomato. Upon co-expressing in cowpea protop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 49 publications
1
60
0
Order By: Relevance
“…This fragment was digested with ClaI and NcoI and cloned into ClaI/NcoI-digested pMON-YFP-Zm7hvr, which encodes the yellow fluorescent protein (YFP) fused to the 40 C-terminal amino acids (the hypervariable region) of Rho of plant 7 from Zea mays (Zm7hvr) (Vermeer et al, 2004).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This fragment was digested with ClaI and NcoI and cloned into ClaI/NcoI-digested pMON-YFP-Zm7hvr, which encodes the yellow fluorescent protein (YFP) fused to the 40 C-terminal amino acids (the hypervariable region) of Rho of plant 7 from Zea mays (Zm7hvr) (Vermeer et al, 2004).…”
Section: Methodsmentioning
confidence: 99%
“…For this, YFP fused to the 40 C-terminal amino acids (the hypervariable region) of Rho of plant 7 from Z. mays (Zm7hvr) (Vermeer et al, 2004), which contains a myristylation site, was used as a marker protein. As expected (Vermeer et al, 2004), protoplasts transfected with pMON-YFP-Zm7hvr, which contains the YFP-Zm7hvr coding region under the control of a double 35S promoter, showed fluorescence mainly in the plasma membrane (Fig. 3a).…”
Section: Mp Molecules Interact Within the Tubulementioning
confidence: 99%
“…As ECFP is not sensitive to photobleaching [35,36], no obvious fluorescence loss was observed for all four ECFP fusion proteins even after 100 iterations of photobleaching with the maximum laser power (data not shown). However, the problem considered most in FRET analysis of living cell is the acceptor mobility, as photobleaching of acceptor fluorophore will cause inhomogeneity in the cellular fluorescent population [37]. Our results showed that the low mobility of acceptor, Myc-E47-EYFP fusion protein, will not interfere with FRET detection in living mammalian cells by the acceptor photobleaching method.…”
Section: The Low Mobility Of Myc-e47-eyfp Fusion Protein In Hek293t Cmentioning
confidence: 83%
“…Combining GFP variants to form good FRET pairs takes some amount of prudence because the excitation and detection ranges are usually quite close so that spectral crosstalk may hinder the accurate determination of FRET efficiencies. These difficulties caused by spectral overlap can be overcome by the detection of the entire spectrum and mathematically unmixing the components (40,41). Another limitation is that most available laser lines are not optimal for excitation, and the GFP variants mostly cover the lower part of the visible spectrum, where autofluorescence greatly limits the sensitivity.…”
Section: Discussionmentioning
confidence: 99%